M28 Frozen section biopsy does not improve benign resection rates in a high-prevalent lung cancer setting. (December 2018) - Dunmore, C; Frost, F; Ledson, M; Walshaw, M; Page, R
Abstract : Introduction: Frozen-Section Biopsy (FSB) allows intraoperative distinction between benign and malignant lung lesions. To minimise lobectomy for benign disease, recent BTS quality standards have suggested that all pulmonary nodules of unknown histology should undergo FSB prior to anatomical lung resection. However, FSB is not possible in all cases and carries with it an increased operative, anaesthetic and resource burden. Liverpool has the highest lung cancer prevalence in the UK and benign resection rates are therefore low. Hence we were interested to investigate the use of FSB in the context of a high lung cancer prevalence setting. Methods: Retrospective analysis of the Liverpool Lung Cancer Unit database was undertaken. We reviewed all patients with undiagnosed pulmonary nodules suspected as being due to T1N0M0 primary cancers whom underwent surgical management Results: In 2017, there were 65 pulmonary nodules suspected as being due to T1N0M0 primary cancers. 46/65 (70%) underwent surgical management and the pathology was unknown prior to surgery in 39/46 (84.8%). FSB was performed in 7/39 (17.9%), for which a primary malignancy was confirmed in all cases. Of the resections without FSB, benign pathology was found in 1/32 (3.1%). In this case FSB had been attempted but was not possible due to position of the lesion; histopathology revealed an organising pneumonia. Median operation time was significantly higher in the FSB group (201.5 min vs. 122.0 min, p<0.0001). Conclusion: FSB rate in our MDT is well below the 100% suggested by BTS quality standards, yet benign resection rates are well within the 10% threshold. FSB was attempted but not technically possible in the only benign resection we observed in 2017. Increasing the use of FSB rate would not alter management in our centre but is likely to significantly increase operative and anaesthetic times. Further work is required to understand the optimal use of FSB in a high-prevalent lung setting.